First observation of the sigma(*+)(c) baryon and a new measurement of the sigma(*+)(c) mass. - Ammar, R; Bean, A; Besson, D; Davis, R; Kwak, N; Zhao, X; Anderson, S; Frolov, V; Kubota, Y; Lee, S; Mahapatra, R; O'Neill, J; et al. (2001)
Using data recorded with the CLEO II and CLEO II.V detector configurations at the Cornell Electron Storage Rings, we report the first observation and mass measurement of the Sigma(*+)(c) charmed baryon, and an updated measurement of the mass of the Sigma(+)(c) baryon. We find M(Sigma(*+)(c))-M(Lambda(+)(c)) = (231.0+/-1.1+/-2.0) MeV, and M(Sigma(+)(c))-M(Lambda(+)(c)) = (166.4+/-0.2+/-0.3) MeV, where the errors are statistical and systematic, respectively.